2020
DOI: 10.1016/j.aninu.2020.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between gut microbiota and antimicrobial peptides

Abstract: The gut microbiota is comprised of a diverse array of microorganisms that interact with immune system and exert crucial roles for the health. Changes in the gut microbiota composition and functionality are associated with multiple diseases. As such, mobilizing a rapid and appropriate antimicrobial response depending on the nature of each stimulus is crucial for maintaining the balance between homeostasis and inflammation in the gut. Major players in this scenario are antimicrobial peptides (AMP), which belong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 124 publications
1
77
0
1
Order By: Relevance
“…In the current study, the obtained results indicated that LPS stimulation not only enhanced the mRNA expression of IL-6 and IL-1β but also enhanced the transcriptional and translational level of iNOS, and further induced intestinal inflammation, which showed consistency with the other reported studies [48,49]. Some studies revealed that gut immunity has been considerably associated with gut microbiota [4,5], and a wide range of gastrointestinal diseases, such as recurrent C. difficile infection (CDI), inflammatory bowel diseases (IBD, including Crohn's disease (CD) and ulcerative colitis (UC)), colorectal cancer (CRC), and metabolic disorders, are affected by the variations observed in the composition and functions of gut microbiota [6,50]. Researchers implied that the variations in gut microbiota between Jinhua and Landrace pigs may contribute to the disease resistance disparity [51,52].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the current study, the obtained results indicated that LPS stimulation not only enhanced the mRNA expression of IL-6 and IL-1β but also enhanced the transcriptional and translational level of iNOS, and further induced intestinal inflammation, which showed consistency with the other reported studies [48,49]. Some studies revealed that gut immunity has been considerably associated with gut microbiota [4,5], and a wide range of gastrointestinal diseases, such as recurrent C. difficile infection (CDI), inflammatory bowel diseases (IBD, including Crohn's disease (CD) and ulcerative colitis (UC)), colorectal cancer (CRC), and metabolic disorders, are affected by the variations observed in the composition and functions of gut microbiota [6,50]. Researchers implied that the variations in gut microbiota between Jinhua and Landrace pigs may contribute to the disease resistance disparity [51,52].…”
Section: Discussionsupporting
confidence: 78%
“…Some studies revealed that gut immunity has been considerably associated with gut microbiota [ 4 , 5 ], and a wide range of gastrointestinal diseases, such as recurrent C. difficile infection (CDI), inflammatory bowel diseases (IBD, including Crohn's disease (CD) and ulcerative colitis (UC)), colorectal cancer (CRC), and metabolic disorders, are affected by the variations observed in the composition and functions of gut microbiota [ 6 , 50 ]. Researchers implied that the variations in gut microbiota between Jinhua and Landrace pigs may contribute to the disease resistance disparity [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as stated, production of AMPs and IgA by Paneth cells in the gut contributes to the host microbiota balance ( 62 , 63 ).…”
Section: Introductionmentioning
confidence: 90%
“…Maintenance of these barriers are essential for preventing microbial invasion, excessive immune responses, and mucosal inflammation. As well as defending against pathogens through competition for nutrients and production of antimicrobial molecules [ 100 , 101 ], the gut microbiota also plays an active role in the maintenance of host mucosal barriers, which further prevents colonisation by opportunistic pathogens, limiting excessive mucosal inflammation, and preserving gut homoeostasis [ 99 , 100 ].…”
Section: The Microbiome and Intestinal Homoeostasismentioning
confidence: 99%